Comparative studies of the degrees of orientation of CO molecules pumped by intense femtosecond two-color pulses based on high-order harmonic generation and Coulomb explosion imaging. (23rd October 2020) - Minemoto, Shinichirou; Komatsubara, Wataru; Sakai, Hirofumi
Abstract: With an intense femtosecond two-color pulse optimized for the generation of even-order harmonics from CO molecules, we directly measure the actual degrees of orientation by utilizing the Coulomb explosion imaging technique with appropriate probe polarization. We find that the macroscopic orientation of CO molecules is negligible even when significant even-order harmonics are observed. This finding shows that the generation of even-order harmonics cannot be ascribed to the macroscopic orientation of CO molecules. The rotational wave packet of CO molecules created with an intense femtosecond two-color pulse is thought to be in an uninvestigated quantum state, which cannot be explained by the theoretical model based on the Born–Oppenheimer approximation, without inversion symmetry at any of the three steps of high-order harmonic generation, leading to the generation of even-order harmonics.